P0301FIT FOR PURPOSE VALIDATION OF A CLINICAL ASSAY FOR THE DETECTION OF SERUM LEVELS OF GALACTOSE-DEFICIENT IMMUNOGLOBULIN A1 (GD-IGA1) IN PATIENTS WITH IGA NEPHROPATHY (IGAN). (6th June 2020) - Sponton, Laura; Jin, Hulin; Fluck, Markus; Suzuki, Yusuke; Kao, Amy
Abstract: Background and Aims: Analysis of serum or plasma from patients with IgA nephropathy (IgAN) has confirmed the presence of elevated levels of circulating immune complexes containing Gd-IgA1 (Czerkinsky 1986). New sensitive and reasonably specific noninvasive tests are emerging to guide the therapeutic strategy that is applicable to all stages of IgAN (Suzuki 2014). Here we are reporting the fit for purpose validation of an ELISA method for the quantitative determination of Gd-IgA1 in human serum samples to support biomarker investigations in clinical studies of Merck KGaA, Darmstadt. Method: The assay was developed based on a commercially available immunoassay kit. The dynamic range of the calibration curve was determined from 1.56 ng/mL (LLOQ) to 100 ng/mL (ULOQ). With a minimum required dilution of 200-fold and standard assay volume of 50.0 μL, the range of the method in matrix was from 312 ng/mL to 20, 000 ng/mL. In assay validation phase, multiple validation parameters were evaluated, which included minimum required dilution (MRD), calibration curve, matrix effect, Intra- & Inter run accuracy & precision, selectivity, and parallelism. Additional validation parameters include sample stability (short/long term, freeze-thaw) and batch-to-batch comparison. Results: All samples measured for intra & Inter - assay precision, accuracy, fulfilled the specifications according to the acceptance criteria. The selectivity was assessed using blank serum matrix from 10 individuals: the result indicated that matrix components in serum did not interfere with the detection of Gd-IgA1. Parallelism assessment was performed successfully for both samples from healthy donors and IgAN patient samples up to dilution factor (DF) 3200 (serum samples from healthy donors were determined up to DF 1600). All DF-corrected results within the assay range were determined with %CV ≤ 30.0%. Batch to batch comparison was assessed successfully based on the known shelf life of the kit. Short term stability using QC samples were given for up to 24hrs at room temperature. Freeze-thaw stability was given for up to 3 cycles at -20°C±5°C and -75°C±15°C. The investigations were performed according to general guidelines for method validation and applicable regulations. The results of investigated validation parameters fulfilled the requirements and recommendations, generally accepted for bioanalytical projects. Conclusion: The present validation qualified the method for the quantitative determination of Gd-IgA1 in human serum samples from clinical studies.